Analysis of Impacts of Crossing Bridges on Flood Control and Dike Safety. Issue 6 (March 2020) - Hui, Teng; Lirong, Wang; Bin, Yan; Bing, Geng
Abstract: The construction of bridges across rivers mostly involves occupying river sections and dike sections, which will adversely affect flood control of rivers and the safety and stability of dikes. Taking an actual project for example, this paper puts forward some ideas and methods for the analysis of impacts of crossing bridges on flood control and dike safety, analyses and evaluates effects of raising of water level, dike foot erosion, seepage stability and anti-sliding stability. Finally, suggestions and measures for bridge construction and dike protection are raised.